Investigating the Training Programs in Pediatric Nephrology: An Experience From Iran: Training Programs in Pediatric Nephrology - Hooman, Nakysa (Journal of Pediatric Nephrology, 2024)
Training in pediatric nephrology officially started in 1990 in Iran, and since then, 143 pediatric nephrologists have been trained. The first curriculum was published in 2009 and has been revised twice. The timetable consists of a two-year program to train them by anticipating the prerequisite clinical skills and problem-solving thinking to apply in their upcoming careers. The training program accepts one fellow per year for each qualified training center. Until now, the ratio of pediatric nephrology is 5.6 per one million children.